Features of formation of motivation for online learning of students of pedagogical specialties - Shrol, Tetiana; Poliukhovych, Nataliia (ScienceRise: Pedagogical Education, 2021)
The concept of "motivation" and modern theories of learning motivation are theoretically substantiated and described: expectancy-value theory, attribution theory, social-cognitive theory, goal orientation theory, self-determination theory. Teaching strategies and pedagogical conditions that motivate students to educational and cognitive activities in the online environment, taking into account the theory of self-determination, are determined. In particular, in order to succeed in mastering something new, a student must feel competent (acquire the appropriate skills to perform practical tasks), related (feel belonging and attachment to groups or individuals), autonomous (feel that he/she controls his/her behavior and is responsible for its goals, capable of self-learning). The pedagogical conditions for the formation of positive motivation and involvement of students in learning online are substantiated and determined, namely: giving a student the opportunity to be an accomplice in the learning process; structuring educational materials in accordance with learning objectives; promoting student initiative and creativity, ensuring group activities and a multidimensional assessment system. The key to fulfilling the pedagogical conditions is the teacher’s motivation to implement online learning at the level of the course author, mentor and tutor for higher education students. External and internal factors of motivation of teachers for introduction of elements of distance (online) and mixed (alternation of online and offline) training by teachers in the educational process of establishments of higher education are defined. Experimentally confirmed: positive impact on the motivation of the implemented online learning strategies and pedagogical conditions; revealed a significant direct relationship between the student’s ability to self-development and self-learning and his/her motivation for online learning